Hepatitis C: A New Future Everyday - Rahman, Salimur (Bangladesh Journal of Medicine, 2016)
Hepatitis C (HCV) is one of the most important cause of liver disease throughout the world, having the potentiality to develop cirrhosis and hepatocellular carcinoma with the passage of time. Recent advances in the management of HCV infection have brought this healthcare burden under limelight. With ongoing research in this field, the future seems to be more promising in the management of HCV infection that has been bothering humanity for decades. Bangladesh J Medicine Jul 2016; 27(2) : 74-77